ANALISIS HUBUNGAN MOTIVASI KERJA, KOMPETENSI DOSEN, KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMITMEN PROFESI TERHADAP KINERJA DOSEN POLITEKNIK KATOLIK SAINT PAUL SORONG - VINA N VAN HARLING; Markus Dwiyanto Tobi (SOSCIED, 2018)
This study aims to analyze the relationship between motivation, competence, leadership, work environment and professional commitment to the performance of lecturer the Saint Paul Polytechnic Sorong by looking at the level of significance of the relationship between each variable. The population used in the study was the Saint Paul Polytechnic lecturer with a number of samples based on Harry King's Nomogram with 95% confidence intervals as many as 54 lecturers with sampling taken by Proportional Random Sampling. Data collection methods used were questionnaires and documentation studies. The results of testing the validity of 6 variables obtained 23 invalid items. The results of the correlation test found a positive and significant relationship between lecturer competency and lecturer performance and also between the commitment of lecturer work and the performance of the Saint Paul Polytechnic lecturer. While for the test results there is no positive and significant relationship found in the correlation test between lecturer work motivation and lecturer performance; between leadership and lecturer performance, and between the lecturer work environment and the performance of the Saint Paul Polytechnic lecturer.